Possible evidence of the radio AGN quenching of neighbouring galaxies at z ∼ 1. Issue 2 (15th January 2019) - Shen, Lu; Tomczak, Adam R; Lemaux, Brian C; Pelliccia, Debora; Lubin, Lori M; Miller, Neal A; Perrotta, Serena; Fassnacht, Christopher D; Becker, Robert H; Gal, Roy R; Wu, Po-Feng; Squires, Gordon
Abstract: Using 57 radio active galactic nuclei (RAGNs) at 0.55 ≤ z ≤ 1.3 drawn from five fields of the Observations of Redshift Evolution in Large-Scale Environments (ORELSE) survey, we study the effect of injection of energy from outbursts of RAGN on their spectroscopically confirmed neighbouring galaxies (SNGs). We observe an elevated fraction of quenched neighbours ( f q ) within 500 kpc projected radius of RAGN in the most dense local environments compared to those of non-RAGN control samples matched to the RAGN population in colour, stellar mass, and local environment at 2σ significance. Further analyses show that there are offsets at similar significance between f q s of RAGN-SNGs and the appropriate control samples for galaxies specifically in cluster environments and those hosted by most massive cluster galaxies, which tentatively suggests that some negative feedback from the RAGN is occurring in these dense environments. In addition, we find that the median radio power of RAGN increases with increasing local overdensity, an effect which may lend itself to the quenching of neighbouring galaxies. Furthermore, we find that, in the highest local overdensities, the f q of the sub-sample of lower stellar mass RAGN-SNGs is larger than that of the higher stellar mass RAGN-SNGs sub-sample, which indicates a more pronounced effect from RAGN on lower stellar mass galaxies. We propose a scenario in which RAGN residing within clusters might heat the intracluster medium (ICM) affecting both in situ star formation and any inflowing gas that remains in their neighbouring galaxies.